Carbon dots from purple sweet potato as a promising anti-inflammatory biomaterial for alleviating the LPS-induced inflammation in macrophages - Jiebang Jiang; Zhiyuan Pan; Yiren Su; Lu Dai; Nana Xu; Han Wu; Xin Chen (Journal of Nanobiotechnology)
Abstract This study synthesizes carbon dots derived from crude extracts of purple sweet potato (CPP-CDs) and evaluates its anti-inflammatory effects in a lipopolysaccharide (LPS) -induced acute inflammation model. Characterization revealed that CPP-CDs possess a uniform spherical structure and excellent photoluminescent properties. In vitro, CPP-CDs significantly inhibited the expression of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α), reduced the accumulation of reactive oxygen species (ROS), suppressed pyroptosis, and facilitated the polarization of macrophages from the M1 phenotype to the M2 phenotype. In vivo, CPP-CDs significantly improved the survival rates of LPS-treated mice, mitigated tissue damage, and suppressed the levels of pro-inflammatory cytokines. Mechanistic studies indicated that CPP-CDs exert anti-inflammatory effects through the inhibition of the TLR4/NF-κB signaling pathway and the modulation of the NLRP3 inflammasome. Additionally, CPP-CDs exhibited excellent biocompatibility, with no significant toxicity observed in mice. This study provides strong evidence supporting the application of CPP-CDs as a novel anti-inflammatory material, highlighting their potential for acute inflammation treatment and expanding the possibilities for the development of carbon-dot-based anti-inflammatory therapies.